SUKARNO'S THOUGHT ON THE IMPORTANCE OF REINTEGRATION OF RELIGION AND SCIENCE IN PESANTREN EDUCATION IN INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2018)
This paper examines Sukarno's thought on the importance of integrating religion and science within Pesantren education. He believes that there should be no separation and dichotomy between religious science and the so called general science as they complement each other. Sukarno's view on this matter was influenced by several things among them is his concern that Pesantren, as an Islamic educational institution, should be an avant garde in promoting the integration between those sciences. In addition, Sukarno also has concern about the condition of the Pesantren at the time; the early twentieth century that, in his opinion, tend to be old fashioned and focuses merely on religious education.